2015
DOI: 10.5430/jnep.v5n8p65
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a nursing handoff educational bundle to improve nursing student handoff communications: A pilot study

Abstract: Background: Inadequate handoff education in prelicensure nursing programs may pose a significant latent safety risk. This pilot study evaluates a Nursing Handoff Educational Bundle (NHEB) for a cohort of Accelerated Bachelor of Science (ABS) nursing students. The Evidence-Based Bundle consists of an educational workshop, a standardized handoff format, clinical faculty education, and structured, formative evaluation of student handoffs. This study was implemented during Adult Health clinical experiences conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Consistently with the current research result [34] describes the necessity of both provider and receiver actively participating in the co-construction of the oncoming caregiver's understanding of the patient in order to promote patient safety. In the same issue [30] found that the nursing handoff educational training program improved handoff communication skills in nursing students.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Consistently with the current research result [34] describes the necessity of both provider and receiver actively participating in the co-construction of the oncoming caregiver's understanding of the patient in order to promote patient safety. In the same issue [30] found that the nursing handoff educational training program improved handoff communication skills in nursing students.…”
Section: Discussionmentioning
confidence: 96%
“…From the researcher's point of view, this result can be explained as, the training program has its immediate positive effect and nurse's intern's starts to apply the knowledge they gained which was reflected on their communication competence, and they recognized pertinent critical health information that needed to be communicated to their peers. In the same issue [30] concluded that nursing students performed significantly better when providing and receiving handoff after they gain handoff knowledge in training program. Additionally, [33] has described the positive effect of handoff training in handoff receiver skills.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The median number of participants in a study was 51.5 (the range was 11–1,206). The studies included 9 pre–post studies, 25 , 51 , 55 , 56 , 58 61 , 65 6 prospective studies, 27 , 52 , 54 , 62 64 1 randomized controlled trial, 53 and 2 observational studies. 9 , 57 Sixteen of the studies reported on interventions undertaken in the United States, and only 1 each reported on an intervention in the United Kingdom 57 and the Netherlands.…”
Section: Resultsmentioning
confidence: 99%
“…Only 4 articles provided details about the educational theory underpinning the intervention, 55 , 57 , 58 , 64 and 10 did not even mention an educational theory. Similarly, only 6 articles clearly explained the pedagogy used for the interventions, 51 , 55 , 57 , 58 , 61 , 62 and 4 did not mention a pedagogy at all. We did find, however, that authors were likely to provide information about context, learners, and teaching approaches.…”
Section: Resultsmentioning
confidence: 99%